On nowhere locally compact spaces with connected Stone - Čech remainder - Arhangel’skii, A. V. (Topology Proceedings, 2021)
In this paper, we present a bunch of results related to the following general question: when is the Stone-Cech remainder of a Tychonoff nowhere locally compact space connected? Several sufficient conditions are given for that. In particular, the case of topological groups is studied. In the last section, a version of the above question is considered in the context of Wallman compactifications of T1-spaces and their remainders. Some open questions are formulated. Dedicated to the memory of Phillip L. Zenor, a fine person and an excellent topologist.